An infant with streptococcal uvulitis presenting with airway obstruction. (2020) - Morooka, Yuya; Furuno, Kenji
Abstract: We report a case of 7-month-old infant girl with severe uvulitis with airway obstruction. Her uvula was erythematous and markedly swollen. Stridor and retraction were noted. The symptoms were resolved after treatment with ampicillin, and a throat swab isolated Group A streptococcus. It is extremely rare in children for uvulitis to cause respiratory distress from airway obstruction. However, in infants with narrow airways, physicians should consider the risk of progression to respiratory distress.